Association between Health Belief Model Constructs and Blood Pressure Control among Hypertensive Patients - Solikhah Solikhah; Dyah Suryani; Ade Riki Hardani Bintang Pertiwi; Maretalinia Maretalinia (Borneo Scientific Publishing, 2026)
Hypertension is a major global health problem and a leading cause of cardiovascular morbidity and mortality, particularly in developing countries such as Indonesia. This study aimed to analyze the association between Health Belief Model (HBM) constructs and sociodemographic factors with blood pressure control among hypertensive patients. A cross-sectional study was conducted in November 2025 at Puskesmas Piyungan, Bantul, involving 219 hypertensive patients selected using purposive sampling. Data were collected using a validated Hypertension Belief Assessment Tool and blood pressure measurements, then analyzed using multiple regression and bivariate tests. Among HBM constructs, only perceived susceptibility was significantly associated with systolic blood pressure (SBP) in multivariate analysis, suggesting a modest inverse relationship between susceptibility beliefs and SBP levels. Sociodemographic factors including age, educational level, and occupational category also showed significant associations with SBP. No HBM constructs were significant predictors of diastolic blood pressure. These cross-sectional findings highlight perceived susceptibility and sociodemographic context as correlates of blood pressure, though the design precludes causal inference. Hypertension management programs should consider patients’ belief profiles and sociodemographic characteristics when designing health promotion interventions, while longitudinal research is needed to confirm the direction and magnitude of these associations.